Community-based Prevention and Control of Myopia in School-age Children: an Explorative Study - Jie WANG, Shiming LI, Dapeng MU, Li ZHANG, Tiantian CHENG, Ningli WANG (Zhongguo quanke yixue, 2022)
Background Myopia is an important cause of visual impairment and has become a public health problem all over the world. In China, myopia has a high incidence rate and age of onset of which is becoming younger. There is no clinical method to reverse myopia in children. Therefore, it is important to standardize the screening for ametropia to realize early detection and intervention of myopia. As a primary care institution, a community health center may accurately understand the prevalence of myopia in teenagers in its service coverage area. So giving full play to the role of community health center has important practical significance for the containment of myopia in children and adolescents. Objective To explore the feasibility of community-based prevention and control of myopia in school-age children. Methods A cohort study was conducted. The information about visual acuity and refractive status of students in a primary school in Beijing's Chaoyang District from September 2019 to September 2021 were collected for statistical analysis, among which four groups of data in September 2019, September 2020, March 2021 and September 2021 were finally included according to the inclusion and exclusion criteria, with a total of 5 558 records. Then, based on the data, an electronic students' refractive database was established, with uncorrected visual acuity, corrected visual acuity, refractive status (power of a spherical lens, power of a cylindrical lens, axis) , prevalence of wearing glasses or orthokeratology incorporated. The warning levels of vision screening were set to be 0, 1, 2 and 3 from low to high. The visual change, visual warning level, spherical equivalent (SE) of students were compared by grade. The visual changes and warning level evolution at different times were compared at the individual level. Corresponding interventions were implemented for different warning levels, and the intervention results were analyzed and discussed. Results There were statistically significant differences in uncorrected distance visual acuity (UDVA) among students by grade (F=100.413, P<0.05) . The UDVA differed significantly in male or female students (F=47.168, 53.042, P<0.05) . Compared with the lower grade students (grades 1 and 2) , middle and higher grade students (grades 3, 4, 5 and 6) had lower UDVA (P<0.003) . The UDVA decreased with the increase in grade in male and female students, and the decline in female students was faster. The composition of the warning levels of myopia risk assessed based on the UDVA in male and female students in all grades was similar, mainly composed of 0, 1, and 3 levels. With the increase in grade, the number of low warning level (level 0) gradually decreased, while that of high warning level (level 3) gradually increased. The SE in students differed obviously by grade (F=474.728, P<0.05) . The SE also differed much in male or female students (F=121.704, 123.807, P<0.05) . With the increase of grade, SE tended to be negative, and the difference in SE between left and right eyes was statistically significant (t=-4.67, P<0.05) . The negative trend of SE for the right eye was more remarkable, suggesting that the warning level of the right eye was higher, and the right eye was more prone to myopia. The follow-up of three consecutive years for assessing individual visual changes revealed that the results of four UDVA screening differed significantly in all students and female students (F=8.727, 10.221, P<0.05) . The UDVA result screened in March 2021 for all students decreased significantly compared with that screened in September 2019 or September 2020 (P<0.008) , so did the UDVA result screened in September 2021 (P<0.008) . During the evolution of warning level, higher warning level was associated with lower possibility of returning to the low warning level, and the possibility of progressing to a higher warning level increased with the growth of warning level. Conclusion The visual acuity and refractive status of students in this primary school in Beijing's Chaoyang District were not optimistic. With the increase in grade, the UDVA decreased and the number of high warning level gradually increased. To actively contain myopia in school-age children, it is suggested to establish a community-based vision screening and warning mechanism, and to promote the containing of myopia by home-school-community collaboration efforts.